2003
DOI: 10.1073/pnas.0306899100
|View full text |Cite
|
Sign up to set email alerts
|

Markov chain Monte Carlo without likelihoods

Abstract: Many stochastic simulation approaches for generating observations from a posterior distribution depend on knowing a likelihood function. However, for many complex probability models, such likelihoods are either impossible or computationally prohibitive to obtain. Here we present a Markov chain Monte Carlo method for generating observations from a posterior distribution without the use of likelihoods. It can also be used in frequentist applications, in particular for maximum-likelihood estimation. The approach … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1,109
0
6

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 1,038 publications
(1,115 citation statements)
references
References 18 publications
0
1,109
0
6
Order By: Relevance
“…This could be accomplished by Approximate Bayesian Computation (ABC) ( Beaumont et al, 2002;Marjoram et al, 2003;Pritchard et al, 1999;Tavaré et al, 1997 ) and lithological tomography ( Bosch, 1999 ). ABC does not require a formal likelihood function and we suspect that this may help to decrease the sensitivity to model errors.…”
Section: Discussionmentioning
confidence: 99%
“…This could be accomplished by Approximate Bayesian Computation (ABC) ( Beaumont et al, 2002;Marjoram et al, 2003;Pritchard et al, 1999;Tavaré et al, 1997 ) and lithological tomography ( Bosch, 1999 ). ABC does not require a formal likelihood function and we suspect that this may help to decrease the sensitivity to model errors.…”
Section: Discussionmentioning
confidence: 99%
“…A more promising approach may be analyses based on summary statistics from the data. Approaches such as approximate Bayesian computation (Beaumont et al 2002;Marjoram et al 2003) using summary statistics suggested by these analytic models may be a powerful way to test hypotheses about the evolution of recombining sex chromosomes. The models developed here cover but a fraction of the diverse sex determination mechanisms known in animals and plants (Bull 1983).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years researchers have devised a variety of methods that seek to detect the population genetic signatures of these demographic events. These include approximate Bayesian computation (ABC) methods, where simulation is used to approximate the posterior probability distributions of a demographic model's parameters through the use of a collection of population genetic summary statistics without specification of an explicit likelihood function (Tavaré et al 1997;Pritchard et al 1999;Beaumont et al 2002;Marjoram et al 2003;Excoffier et al 2005;Wegmann et al 2010). Other approaches, such as diffusion approximations for demographic inference (@a@i) (Gutenkunst et al 2009), use the probability density of the site frequency spectrum (SFS) under a given demographic model and parameterization to calculate the likelihood of the observed SFS (Marth et al 2004;Gutenkunst et al 2009), thereby allowing for optimization of model parameters.…”
mentioning
confidence: 99%